Elimination of grain boundary resistance in vanadoborate electrolyte via the hydrogen-bond interaction of glycerol. Issue 29 (22nd March 2023) - Zhang, Shan; Lu, Ying; Sun, Xiu-Wei; Tian, Hong-Rui; Bai, Xue; Liu, Shu-Xia
Abstract : The addition of glycerol into a pellet of VB electrolyte can effectively eliminate its grain boundary resistance and make its proton conductivity approach the intrinsic conductivity indicated by a VB single crystal. Abstract : An effective method to eliminate grain boundary resistance of crystalline vanadoborate electrolyte was developed. This method involved the addition of glycerol to result in the formation of many hydrogen bonds between crystal grains, facilitating a rapid transfer of protons across grain boundaries. Using this method, the intrinsic conduction of vanadoborate electrolyte was fully reflected in its bulk materials, valuable for advancing our understanding of vanadoborate electrolytes and for promoting the application of these electrolytes.